Migration model to Cloud Computing in higher level educational institutions - Carrasco Ore, Nilo Eloy (2023)
The need of many companies to improve their effectiveness and efficiency translates into the demand for migration to Cloud Computing, not being exempt from this the higher level educational institutions which record and store a large amount of data requiring investment in resources in all related to information technology. The present work has as main objective the design of a migration model to Cloud Computing which was called PMC to facilitate this process, this model was applied to an educational institution, where goals such as minimizing costs were achieved, obtaining results without delays and within the planned costs, the process time was reduced, obtaining short-term results showing the satisfaction of the users in the use of the systems, a survey was applied to the administrative personnel who interact with the systems that were migrated. The work was carried out considering a non-experimental methodology with a quantitative approach.